Spatial dynamics of the Serra do Gandarela and around: an analysis from representations coremáticas - Fonseca, Charles de Oliveira; Valadão, Roberto Célio (Sociedade & Natureza, 2017)
This work employs the chorematic modeling as methodological procedure liable to present the spatio- temporal dynamic of the Gandarela Ridge and surroundings. Such modeling interacts with geographical concepts that once mobilized, become possible the use of analytical categories necessary for understanding spatial organization by means of graphic images. Therefore, the chorems presented aim to transcend the information communicated through conventional maps. Opposing to the current economic, mineral and enviromental reality of the Quadrilátero Ferrífero, the Gandarela Ridge is nowadays the latest natural remaining in good state of repair in this region of Minas Gerais. In the vicinity of this ridge, there are local communities that do use areas for subsistence production, collection and extraction. In this scenario, in the last couple of years, polarized pressure fields have been formed: on one hand mining companies and eucalyptus producers claim the legalization of the land use for their core activities; on the other hand, environmentalists, researchers and local residents, with the support of the ICMBio and NGOs, have positioned themselves in favour of the creation of the Parque Nacional do Gandarela and a sustainable development reserve. Those vindications and placements have established territorial pressures that set the current and complex environmental framework of the investigated area, marked by conflicting interests of multiple actors and consequently by conflict and spatial changes, registered here in chorematics models.